Costs, Benefits and Obstacles to the Adoption and Retention of Shelterbelts: Regional Perception and Mind Map Analyses for Ukraine - Popov, Andriy; Tymoshevskyi, Vladyslav; Poliakh, Vadym (Geomatics and Environmental Engineering, 2022)
The role of shelterbelts within an agricultural landscape is changing significantly. In the past, shelterbelts have been encouraged and established to reduce soil erosion and increase crop yields. Land reform (land privatisation) and advances in production technology led to increases in agricultural holding size. This requires a revision of policy concerning shelterbelt management in rural communities, especially since there is no recent research on community perceptions regarding the adoption and retention of shelterbelts. The specific objective of this research was to identify the public costs, benefits and obstacles from the adoption and retention of shelterbelts. In the summer of 2019, a survey was conducted of territorial communities (hromadas) in Ukraine. It was observed that many of the benefits of shelterbelts were classified as noneconomic. Therefore, these benefits are more difficult for the leaders of hromadas to recognise within their management decisions. The costs to hromadas were identified and strongly affected management decisions but the actual monetary costs were not identified. Shelterbelts have the potential to mitigate climate change yet most hromadas do not recognise the social and environmental benefits of shelterbelts within their management decisions.